Producción de juveniles infectivos de Heterorhabditis spp. usando como hospederos Spodoptera frugiperda J.E. Smith y Galleria mellonella Linnaeus - Solano Plasencia, Sandra Giuliana (2019)
The present research work entitled "Level of production of infective juveniles of Heterorhabditis spp. using Spodoptera frugiperda and Galleria mellonella as hosts "aimed to determine the level of production of infective juveniles of Heterorhabditis spp._x000D_ The breeding of Spodoptera frugiperda and Galleria mellonella was carried out to obtain larvae of the last stage, which were infected with juveniles of Heterorhabditis spp. obtaining entomopathogenic nematodes that were collected and accounted for._x000D_ It was determined that G. mellonella larvae produce an average of 326 280 infective juveniles, contrary to S. frugiperda, which produces only 225 776 infective juveniles._x000D_ The highest percentage of larval infection was obtained in Galleria mellonella being 98%, while in Spodoptera frugiperda only 78% of the evaluated larvae were infected.